Trepanation and artificial cranial deformations in ancient Armenia - Khudaverdyan, Anahit (Anthropological Review, 2011)
The purpose of the paper is to review surgical and ritual practices on people living on the Shirak Plateau (Armenia) during the Late Antiquity period (1st century BC – 3rd century AD) and is based on human remains uncovered at sites in Beniamin, Black Fortress I, Shirakavan, Karmrakar and Vardbakh. The basic demographic data for these cases, including the age and sex of the skeleton, the precise location of the trepanation, the form of the trepanation and instruments used, and the presence of any associated pathologies, injuries, diseases, or developmental deformities on the skeleton, are specified. The phenomenon of artificial skull and teeth modifications identified at ancient burials sites in Armenia clearly points to the emergence of social complexity and class differentiation, and hence the need for social distinction, which in this case was accomplished through the use of body markings. A compilation of case reports and information on trepanation and deformation is essential for a bioarcheological study of the procedure.